ANALISIS NILAI TAMBAH PENGOLAHAN KEDELAI MENJADI SUSU KEDELAI PADA INDUSTRI RUMAH TANGGA SARI KEDELAI “BU ADE” DI CATURTUNGGAL KEC. DEPOK KABUPATEN SLEMAN DIY - Dwi Yuliyanto; Susi Widiatmi; Nanang Kusuma Mawardi (Fakultas Pertanian UST, 2023)
This study aims to determine the process of processing soy into soy milk and to find out the added value that exists in the Household Industry of Soy Essence